2015
DOI: 10.1038/srep16589
|View full text |Cite
|
Sign up to set email alerts
|

Improved anti-glioblastoma efficacy by IL-13Rα2 mediated copolymer nanoparticles loaded with paclitaxel

Abstract: Glioma presents one of the most malignant brain tumors, and the therapeutic effect is often limited due to the existence of brain tumor barrier. Based on interleukin-13 receptor α2 (IL-13Rα2) over-expression on glioma cell, it was demonstrated to be a potential receptor for glioma targeting. In this study, Pep-1-conjugated PEGylated nanoparticles loaded with paclitaxel (Pep-NP-PTX) were developed as a targeting drug delivery system for glioma treatment. The Pep-NP-PTX presented satisfactory size of 95.78 nm wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Blood samples were collected after 24 h for hematologic and histochemical analysis. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood urea nitrogen (BUN) and creatine kinase isoenzyme (CKMB) levels were assayed 25 using a Fujifilm DRI-CHEM NX500i Analyzer (Fujifilm, Tokyo, Japan).…”
Section: In Vivo Toxicity Evaluation and Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected after 24 h for hematologic and histochemical analysis. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood urea nitrogen (BUN) and creatine kinase isoenzyme (CKMB) levels were assayed 25 using a Fujifilm DRI-CHEM NX500i Analyzer (Fujifilm, Tokyo, Japan).…”
Section: In Vivo Toxicity Evaluation and Histologymentioning
confidence: 99%
“…Moreover, most of the intravenously injected NPs are taken up and taken up and eliminated by RES organs which includes liver and kidneys. 25 Therefore, AST and ALT for hepatic function, BUN for kidney function and CKMB as cardiac markers were measured on day 1 and day 7 after treatment injection.…”
Section: In Vivo Safety Evaluationmentioning
confidence: 99%
“…46 Presumably, further modifications of the surface of CS-DX-SPIONs with targeting bioligands (eg, antibodies, peptides, proteins, etc) could further increase the accumulation of particles inside glioma tissue. Previously, several studies demonstrated that coating with tumortargeting molecules including anti-Hsp70 antibody, 16 peptide-targeting interleukin-13 receptor α2 (IL-13Rα2), 47 anti-VEGF antibodies, 48 antibodies toward EGFR deletion mutant (EGFRvIII), 49 anti-insulin-like growth factor binding protein 7 (anti-IGFBP7) single domain antibody, 50 and many others could show an enhanced particle retention inside tumor cells. [51][52][53][54]…”
Section: Discussionmentioning
confidence: 99%
“…The PLGA nanoparticles exhibited long circulation and deeper penetration in glioma spheroids. However, for the in vivo distribution, higher concentration of the injected nanoparticles accumulated in liver and spleen [57] . This greatly reduced the sufficient drug entry into brain tumor.…”
Section: Polymer Nanoparticlesmentioning
confidence: 97%
“…It had been applied in many delivery systems against various diseases, including tumors. Also, the PLGA nanoparticles prepared by nano-emulsion could be played as efficient carriers across the blood-brain barrier [45] , [57] , [58] . For example, a cyclic nine amino peptide, CRTIGPSVG (CRT), was introduced into poly(ethylene glycol)-poly( d , l -lactic- co -glycolic acid) (PEG-PLGA) [59] , with a final diameter of 118.8 nm.…”
Section: Polymer Nanoparticlesmentioning
confidence: 99%